Do the Bangladeshi Banks Move Forward to Integrated Reporting Culture?: A comparative Analysis between Bangladeshi and South African Banks - Tanmay Biswas (Jurusan Akuntansi Politeknik Negeri Bandung, 2023)
The goal of the research is to assess the disclosure quality of integrated reporting practices for both Bangladeshi Banks and South African Banks over time. This paper is based on a scoring model, referencing the framework proposed by Hammond and Miles (2004), and identified an IR Scoreboard (IRS), divided into four sections. For the reason of the IRS, authors have analyzed, 105 integrated reports of 15 listed banks, ten from Bangladesh and five from South Africa, IIRC framework issued in 2021. A seven-year observation of each bank from 2015 to 2021 has been collected. In this study, we consider simple random sampling for data collection. The analysis suggests that majority of the Bangladeshi banks implement integrated reporting with low quality. From the elements in the background area, it is observed that Bangladeshi banks paid medium attention to the reasons behind adopting IR which is 52.9% but for South Africa, it is 100%. The content elements performed within 27.1% to 95.7% for Bangladeshi Banks whereas, for South African banks, it was within 0% to 100%. IR may take more time to adopt. For Bangladeshi banks, IR is still in the initial stages of development. But, South African banks maintain consistency in integrated reporting practices.